Awareness in Action : Self-Awareness and Group Process - Philipson, Phylis J.; Gary, Juneau Mahan (University Press of America, 2015)
Awareness in Action is a user-friendly text/workbook designed to provide individuals with an increased understanding of themselves and others. Using group-based experiential exercises to enhance self-awareness in professional and personal relationships, the workbook is crafted to guide those wishing to improve the quality of both types of relationships.